Réponses

2012-12-05T22:18:08+01:00

g=(4t+1)(4t-1)-(3t+2)²

g= (4t+1)(4t-1)-(3t+2)(3t+2)

g=16t²+4t+4t+1-9t²+6t+6t+4

g=7t²+20t+5

 

Tu fait pareil pour les autres même étapes ! :) Copie mon modéle

Meilleure réponse !
2012-12-05T22:32:49+01:00

g= (4t+1)(4t-1)-(3t+2)²

4t*4t+4t*(-1)+1*4t+1*(-1)-(3²)t+2*3t*-2²

16t²-4t+4t-1-9t²-12t-4

7t²-12t-5

 

h=2(s+5)(s-5)+(4s+3)²

(2*s+2*5)(s-5)+(4²)s+2*4s*3+3²

(2s+10)(s-5)+16s²+24s+9

2s*s+2s*(-5)+10*s+10*(-5)+16s²+24s+9

2s²-10s+10s-50+16s²+24s+9

18s²+24s-41

 

i= (3t+4)²-(1-2t)(6+t)

(3²)t+2*3t*4+4²-1*6-1*t+2t*6+2t*t

9t²+24t+16-6-t+12t+2t²

11t²+35t+10